2015
DOI: 10.1016/j.msec.2015.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite-based materials of marine origin: A bioactivity and sintering study

Abstract: Single phase hydroxyapatite (HAp) and biphasic material hydroxyapatite/β-tricalcium phosphate (HAp/β-TCP) were obtained from a marine source (Atlantic cod fish bones). Here we report a study on the biological properties of these materials, including cytotoxicity, bioactivity and haemocompatibility. Results showed that the materials are not cytotoxic, neither in their powder nor in pellet form; indeed growth of Saos-2 cells was comparable to that of commercial. The haemolysis rate was lower than 2%; hence the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 30 publications
2
38
0
Order By: Relevance
“…Samples treated at 700°C and at 1100°C having the lowest and highest content of Eu, were selected for this study; for comparison samples without Eu prepared with the same protocol (i.e., extracted from codfish bones thermally treated at the same temperatures but without Eu incorporation) were assessed as well. This was done to assess whether the presence of Eu affected the cell viability of these CaP phases, whose biocompatibility was already proven . In detail, 24 hours after cells seeding, the selected powders (i.e., A, B, Eu1, Eu2, Eu7, and Eu8) were added to the culture medium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples treated at 700°C and at 1100°C having the lowest and highest content of Eu, were selected for this study; for comparison samples without Eu prepared with the same protocol (i.e., extracted from codfish bones thermally treated at the same temperatures but without Eu incorporation) were assessed as well. This was done to assess whether the presence of Eu affected the cell viability of these CaP phases, whose biocompatibility was already proven . In detail, 24 hours after cells seeding, the selected powders (i.e., A, B, Eu1, Eu2, Eu7, and Eu8) were added to the culture medium.…”
Section: Resultsmentioning
confidence: 99%
“…The bones of codfish, which is one of the most popular and traditional fish species consumed around the world, were also investigated to recover CaP based compounds . Recent studies have demonstrated that CaP phases in the form of pure HAp or HAp/β‐TCP biphasic material, with biocompatibility comparable to that of commercial samples, can be easily extracted from codfish bones by a simple calcination process …”
Section: Introductionmentioning
confidence: 99%
“…Although, as we noted above, many bioactivity tests for the growth of HAp in SBF in similar bioglasses do not actually present hard evidence of crystallization of HAp through XRD or SEM images, one of the authors has published an article previously on the crystallization and growth of HAp in SBF on sintered pellets of HAp derived from marine wastes . These showed a clear growth of HAp between 3 and 7 days, much less than the 2–4 weeks required with these materials, although it also must be stressed that these were pure HAp ceramics, which were themselves highly crystalline after being sintered at 700°C.…”
Section: Resultsmentioning
confidence: 97%
“…The acid-insoluble calcium silicate hydrates synthesized from oyster shells were also applicable in removing organic pollutants and heavy metal ions 90 . Single-phase hydroxyapatite (HA) and biphasic calcium phosphate (HA/β-TCP), which are derived from Atlantic cod bones, have no known cytotoxic effects and have demonstrated good bioactivity in simulated body fluid 91 . Consequently, calcium phosphate derived from marine organisms has a promising future in fabricating bacterial infection-resistant bone substitutes or bone defect healing.…”
Section: Other Functions Of Marine Source Calciummentioning
confidence: 99%